Pengaruh Kesadaran Pajak dan Pengetahuan Pajak Terhadap Kepatuhan Wajib Pajak pada Karyawan PT Surveyor Indonesia - Cahyo Hadi Arrosyid; Bambang Soedaryono (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This research aims to determine the influence of tax awareness and tax knowledge on taxpayer compliance of PT Surveyor Indonesia employees. This research uses quantitative methods with a sample of 98 respondents. The results of this research indicate that tax awareness has a significant influence on taxpayer compliance of PT Surveyor Indonesia employees. Tax knowledge has a significant positive influence on taxpayer compliance of PT Surveyor Indonesia employees. Tax awareness and tax knowledge, both together and individually, have a significant positive effect on taxpayer compliance of PT Surveyor Indonesia employees.